Digital modeling evaluation on tidal effect of the Galing River - Amirul Juwaidy, Omar (2010)
Galng River has been spotted by the Drainage and Irrigation of Department of Pahang as one of the high potential area to be effected by flood. This river was chosen by the state government for the "1 State 1 River" program. Flood is one of the main disasters in this country it basically occurs at any reach of a river due to different factors. In the 14pstrcam area it i.stiai1y caused by the dischar g e which exceed bank flow and that discharge cannot be sustained by river cross section and river bed. Whereas flood occurs in estuary area is caused by the tidal influences. Analysis of the Galing River was conducted using the Info Works RS (river simulation) program software. The analysis is based on the rainfall and tidal data taken from the Drainage and Irrigation of Department for Kuantan area and the cross section of the river. Scope of this study included the location area, data input fOr, each event and water level simulation of the river. The simulation were analysed in three conditions. In the first analysis, the simulation is carried out at high and low tidal. In the second analysis, the simulation is carried out at high tidal with 50 Affi and 100 ARI rainfall events. In the third analysis, the simulation was carried out at high tidal with existing bridge. The results of the simulation showed that flood occured at the downstream of the river during high tidal, The recorded data at each chainage showed that the water levels increase as the flow increases.